Effects of HydrotherapyLemongrass (Cymbopogon Citartus) On Blood Pressure in Elderly People with Hypertension At the Tuntungan Community Health Center, Pancur Batu District - Herianto Bangun; Dameria Br Ginting (International Journal of Health and Pharmaceutical (IJHP), 2025)
Hypertension or high blood pressure, this disease can attack anyone, both young and old. Hypertension (high blood pressure) is a medical condition characterized by systolic pressure greater than 140 mmHg and diastolic pressure greater than 90 mmHg. Efforts to prevent blood pressure problems are not only through medication, but also through complementary medicine to treat high blood pressure. Lemongrass foot hydrotherapy is a natural treatment that improves blood circulation by widening the blood vessels and improving blood circulation, which then stimulates the nerves in the feet, stimulating the activation of the sympathetic nerves and improving blood circulation. Quasi Experimental Method with pre test and post test with control group design. In two groups intervention and control (without treatment). Done for 3 days. The sample was 20 respondents. The results of bivariate analysis with 2 tests, namely the Wilcoxon test, showed a p value = 0.005 (p value 0.05), and the Man Whitney test showed a p value = 0.001 (p value 0.05). Therefore, it can be concluded that foot hydrotherapy with lemongrass is useful in lowering blood pressure in elderly people suffering from high blood pressure at the Community Health Center in the Tuntungan District. Pancur Batu, so that health center health workers can use complementary medicine as an alternative to lowering blood pressure for people with high blood pressure because it is easy and cheap from an economic perspective.